Networks of Displacement: Comparative Histories of Forced Migration and Cultural Adaptation in the Indian Ocean World (16th–19th Century) - Nimesha Ekanayaka; Waqas Minhas; Hina Sattar; Saima Yasmin (Indus Journal of Social Sciences, 2025)
The Indian Ocean world has historically served as a vibrant arena for migration, commerce, and cultural interaction, yet the dynamics of forced migration within this region remain insufficiently explored. This study aims to investigate the patterns and impacts of coerced mobility between the 16th and 19th centuries, particularly under Portuguese, Dutch, and British colonial regimes. Through a comparative framework, the research analyzes how displaced populations, including African slaves, Indian convicts, and war captives, navigated the complexities of transplantation, adaptation, and cultural retention across diverse maritime contexts. The findings indicate that despite systemic exploitation, displaced groups cultivated resilient cultural identities, established diasporic networks, and contributed significantly to the urban, religious, and economic transformations of key port cities such as Colombo, Batavia, and Zanzibar. Discussions underscore how forced migrants facilitated hybrid cultural practices, informal economies, and religious syncretism, challenging monolithic views of colonial domination and presenting the Indian Ocean as a space of multidirectional agency rather than passive subjugation. By framing forced migration within the larger currents of maritime and global history, this study critiques Eurocentric models of displacement and labor historiography, emphasizing the active role of marginalized groups in historical processes of globalization. It concludes that forced migration, far from being a peripheral phenomenon, was socio-economic landscapes in the Indian Ocean world. Future research is recommended to expand comparative analyses across additional colonial contexts and to integrate archaeological and linguistic evidence, offering a more holistic understanding of the enduring legacies of forced mobility in shaping modern global interconnections.